On the (In)Compatibility of Attitudes Toward Peace and War. Issue 5 (22nd February 2013) - Bizumic, Boris; Stubager, Rune; Mellon, Scott; Van der Linden, Nicolas; Iyer, Ravi; Jones, Benjamin M.
<x xml:space="preserve">Abstract</x> Although attitudes toward peace and war are usually treated as two opposite poles of one dimension, in this article we argue that they may represent two distinct dimensions. To investigate this idea, we developed and tested a new balanced measure, the Attitudes Toward Peace and War (APW) Scale, in three studies (N = 4, 742) in the United States and Denmark. Exploratory and confirmatory factor analyses showed that attitudes toward peace and war formed two distinct, though negatively related, factors. Structural equation modeling showed that antecedents of attitudes toward peace included egalitarian ideological beliefs, the values of international harmony and equality, and empathic concern for others, and consequences included intentions to engage in peace‐related activities. On the other hand, antecedents of attitudes toward war included authoritarian ideological beliefs, the values of national strength and order, and less personal distress, and consequences included intentions to engage in warlike activities. Results also showed that political affiliation had an impact on the relationship between peace and war attitudes, with conservatives less likely to find the attitudes incompatible. The findings support the view that attitudes toward peace and war represent two distinct dimensions.